Performance of Embodied Fragments - Fight, Flight, Freeze (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article analyzes the fragmented presence of body artists in contexts where the iconographies of violence attack notions of integrity, displaying bodies as Necromessages. Who are the artists? What are the works we speak of in contemporary theater, understanding that memory preserves the trauma of violence on fragmented bodies? An research of performances was carried out, cataloged into three response patterns of the organism when facing danger: Fight, Flight, and Freeze. Far from being a psychological view of art, the analysis focuses on the artists and how, in practice of Performance Art, they embody their experiences, legitimising the very conception of narratives of pain, war, trauma and terror in the contemporary scene.
Keywords: performance art; body; violence; trauma; corporeity